Shift ahead : how the best companies stay relevant in a fast-changing world - Adamson, Allen P.; Steckel, Joel H. (AMACOM, 2018)
The future is closer than you think. In a world that's changing faster and more furiously than ever, the ability to shift focus is critical. Why is it that some organizations can continually evolve to meet the times and the marketplace, and others can't? How do some businesses recognize the right moment to shift, and others, ruefully, only after it's too late? Packed with insightful interviews, Shift Ahead offers a smart, calculated approach to knowing when to change course and how to pull it off. The book brings every internal and external factor into view: competitors, risks, culture, finances, and more. And it taps success stories and cautionary tales -- including HBO, Adobe, BlackBerry, National Geographic, NYU, Microsoft, Kodak, and P&G -- to explain how to: Spot warning signs that it's time for reinvention Overcome obstacles in the way of future goals Maintain authenticity when changing gears Execute a bold change seamlessly To stay competitive, you must shift; to stay credible, you must focus. Shift Ahead turns this difficult maneuver into a straightforward strategy.